Studies on gliclazide β-hydroxypropylmethylcellulose complexes and its tablets - Aggarwal S.; Rani M.; Srivastava A.K.; Mishra B. (My University, 2025)
Formation of gliclazide (Gz) complexes with β-cydodextrin (β-CD) in solution form, with and without the addition of water-soluble polymers was studied by phase solubility method. The stability constant (Kc) was found to be 1617.7 M-1 for Gz-β-CD complex in 1:2 molar ratio. Solid complexes of Gz were also prepared by autoclaving, neutralization, kneading and physical mixing methods in 1:1 and 1:2 Gz-β-CD molar ratios. The complexes containing 0.05% w/w hydroxypropylmethylcellulose and prepared by autoclaving method exhibited better Gz dissolution. Fabricated tablets of pure Gz and of different complexes and two commercial tablets were evaluated in vitro. Tablets containing complexed Gz dissolved much faster than pure Gz and commercial tablets. Incorporation of small amount of hydroxypropylmethylcellulose in Gz-β-CD complexes further enhanced the rate and extent of drug dissolution.